Observaciones sobre el surgimiento del primer techo urbano leonés - Reguera Rodríguez, Antonio Teodoro (Estudios humanísticos. Geografía, historia y arte, 2021)
Rome tries to systematize the guidelines of colonial rule in the NW of the lberian Peninsula by establishing schemes of spatial organization, in which military camps are included as the nuclei of highest strategic value in controlling and integrating the productive forces. The first towns in Leon developed according to these determinants.